Generalized Interpolative Contractions and an Application. (15th November 2021) - Nazam, Muhammad; Aydi, Hassen; Hussain, Aftab
Abstract : In this study, we introduce a property ( P ) and the generalized interpolative contractions of types I, II, III, and IV. We investigate certain conditions for the existence of fixed points of generalized interpolative contractions. We derive several new results from the main theorems. As an application, we resolve the Urysohn integral equation.